A Review of Some Recent Advances in the Use of Cheiloscopy and Dermatoglyphics for Forensic Investigations - O., Mosugu O.; F., Otashu K.; I., Salman J.; W., Nsisong S.; W., Alfred A.; O., Ajayi S.; E., Bright C.; M., Jibaniya G.; S., Katchin E.; J., Tongle N. (Darul Yasin Al Sys, 2025)
The field of forensic investigation has advanced significantly, particularly in developed countries, with new technologies enhancing the reliability of human identification. This review highlights recent innovations in lip printing (cheiloscopy) and fingerprinting (dermatoglyphics), focusing on their application in forensic science. While dermatoglyphics remains a conventional method, cheiloscopy has emerged as a complementary, less conventional tool for investigation and research. Recent developments incorporate artificial intelligence (AI) and machine learning (ML) techniques, which have improved the accuracy and efficiency of forensic analyses. Multimodal biometric systems that integrate cheiloscopy and dermatoglyphics further reduce error rates and increase reliability, offering stronger fraud resistance. Despite these advancements, many developing countries have yet to fully adopt or master AI- and ML-based forensic tools, limiting their application in real-world investigations. The review concludes that integrating these technologies into forensic practice has the potential to significantly improve human identification, though challenges related to accessibility, expertise, and infrastructure must be addressed.